Comparison of encrustation between silicon-covered and polytetrafluoroethylene-covered metallic stent, in vitro experimental study - Deok Hyun Han; Woo Jin Bang; Jae Hoon Chung (Investigative and Clinical Urology)
Purpose: To compare encrustation resistance between silicon- and polytetrafluoroethylene (PTFE)-covered metallic ureteral stents (MUS) in an in vitro infection model and to determine the most effective material for reducing biofilm formation and encrustation. Materials and Methods: A total of 52 MUS were prepared: 26 silicon-covered and 26 PTFE-covered stents. Each sample was immersed in artificial urine inoculated with Proteus mirabilis in a biofilm reactor for 48 hours. After immersion, the stents were weighed to measure their encrustation level. Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) were used to assess the surface morphology and elemental composition of the encrustation deposits. Results: Silicon-covered stents showed a statistically significant reduction in weight gain due to encrustation compared to PTFE-covered stents (9.50±5.77 mg vs. 16.75±10.61 mg; p=0.004). Additionally, encrustation per unit length was lower in silicon-covered stents (0.76±0.45 mg/mm vs. 1.30±0.81 mg/mm; p=0.004). SEM and EDS analyses demonstrated lower calcium salt deposition on the silicon-covered stents, indicating greater resistance to encrustation. Conclusions: Silicon-covered MUS demonstrated superior resistance to encrustation compared to PTFE-covered stents, supporting silicon as a more suitable covering material for long-term MUS applications. This finding may lead to extended stent lifespans and a reduced frequency of stent replacements, benefiting both patients and healthcare systems.